EFFECT OF CLAIMS PAYMENTS ON PROFITABILITY IN THE NIGERIAN INSURANCE INDUSTRY - Afolabi, Taofeek Sola (Advances in Social Sciences Research Journal, 2018)
Profitability determines an insurance company’s ability to make claims payments as at when due. The objective of this study is to examine the effect of claims payments on the profitability of insurance companies in Nigeria. Secondary data were generated from the financial statements of the two selected insurance companies, covering the periods 2011 to 2016. Using descriptive statistics and the multiple regression techniques, the data was analyzed with the aid of the Statistical Package for Social Sciences (SPSS version 23). The result reveals that ROA (profitability) has an indirect relationship with LR (loss ratio) and NC (net claims), but a direct relationship with ER (expense ratio). It further reveals that net claims have a significantly positive impact on loss ratio. The study recommends that the Nigerian insurance industry must effectively manage their claims processes, in order to reduce the amount of claims for every earned premium.